2017
DOI: 10.1016/j.addbeh.2016.08.028
|View full text |Cite
|
Sign up to set email alerts
|

Effects of depressive symptoms and coping motives on naturalistic trends in negative and positive alcohol-related consequences

Abstract: Objective Depressive symptoms and drinking to cope with negative affect increase the likelihood for drinking-related negative consequences among college students. However, less is known about their influence on the naturalistic trajectories of alcohol-related consequences. In the current study, we examined how positive and negative drinking-related consequences changed as a function of depressive symptoms and drinking motives (coping, conformity, social, enhancement). Method Participants (N = 652; 58% female… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
16
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 57 publications
(54 reference statements)
1
16
0
Order By: Relevance
“…Consistent with previous studies on substance use motives for single substance users of alcohol or marijuana (Blevins et al, 2016;Farris et al, 2016;Kenney et al, 2015Kenney et al, , 2017, the present study found that for college students who use both alcohol and marijuana, substance use motives mediate the relationship between negative affect and substance use outcomes. In particular, coping motives were found to mediate the association between depressive/anxiety/stress symptoms and alcohol and marijuana consequences, lending further support to the negative reinforcement models that assert that people use substances as a means of mitigating negative affect (e.g., Baker et al, 2004;Greeley & Oei, 1999;Khantzian, 1997;Sher & Levenson, 1982).…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Consistent with previous studies on substance use motives for single substance users of alcohol or marijuana (Blevins et al, 2016;Farris et al, 2016;Kenney et al, 2015Kenney et al, , 2017, the present study found that for college students who use both alcohol and marijuana, substance use motives mediate the relationship between negative affect and substance use outcomes. In particular, coping motives were found to mediate the association between depressive/anxiety/stress symptoms and alcohol and marijuana consequences, lending further support to the negative reinforcement models that assert that people use substances as a means of mitigating negative affect (e.g., Baker et al, 2004;Greeley & Oei, 1999;Khantzian, 1997;Sher & Levenson, 1982).…”
Section: Discussionsupporting
confidence: 91%
“…Multiple theories/models (e.g., stress-dampening model, Sher & Levenson, 1982; tensionreduction model, Greeley & Oei, 1999; self-medication hypothesis, Khantzian, 1997; affective-motivational model of drug addiction, Baker, Piper, McCarthy, Majeskie, & Fiore, 2004) posit that individuals engage in substance use because they expect that using that substance provides immediate coping benefits by alleviating their negative affect. In support of these theories, multiple studies among college students have found that substance use motives (for a review of substance use motives, see Cooper, Kuntsche, Levitt, Barber, & Wolf, 2016), particularly coping motives, mediate the associations between negative affect and both alcohol (Blevins, Abrantes, & Stephens, 2016;Kenney, Jones, & Barnett, 2015;Kenney, Merrill, & Barnett, 2017) and marijuana (Farris, Metrik, Bonn-Miller, Kahler, & Zvolensky, 2016) outcomes. Taken together, existing research has supported coping-motivated substance use for these students when examining alcohol-and marijuana-related problems separately.…”
Section: Introductionmentioning
confidence: 99%
“…For example, it would be interesting to see whether reductions in stress or depressive symptoms lead to reductions in demand and craving and increases in future orientation. Further, it is possible that individuals experiencing elevated levels of depression or stress are evaluating or interpreting their drinking‐related behaviors and problems more negatively than someone who is not experiencing this same level of symptoms (Kenney et al., ). As such, this bias may affect how these individuals interpret the items on the alcohol problems measure and how they report on their own drinking‐related behavior and problems.…”
Section: Limitations and Future Directionsmentioning
confidence: 99%
“…Also, directions on the DMQ-R for the high school students did not refer to a specific timeframe; for college students, motives were placed in the context of the past 2 weeks. Both Kuntsche and Kuntsche (2009), who asked respondents to consider "the last 12 months," and Kenney, Merrill, and Barnett (2015), who asked respondents to consider the "past 30 days," also instructed participants to base their responses on specific time frames when completing the DMQ-R. Careful comparison of mean DMQ-R subscale scores for the college student sample ( Supplementary Table S2) showed negligible differences relative to other investigations of underage drinking motives (the same was true for the high school sample as well; see Supplementary Table S3).…”
Section: Limitations and Future Directionsmentioning
confidence: 99%